Physicochemical and Sensory Characteristics in Noni Coffee Beans (Morinda citrifolia L.) with Arabica Coffee Substitution (Coffea arabica): Karakteristik Fisikokimia dan Sensori Kopi Biji Mengkudu (Morinda citrifolia L.) dengan Substitusi Kopi Arabika (Coffea arabica) - Ajeng Nurfitria; Hutami, Rosy; Hapsari, Distya Riski (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Noni seeds are known to be rich in antioxidants and bioactive compounds, making them a promising ingredient for the development of functional food products, such as noni bean coffee. This study aimed to evaluate the effect of different ratios of noni bean coffee to Arabica coffee on the physicochemical and sensory properties of the final coffee product. A Completely Randomized Design (CRD) with one factor was applied, consisting of four treatment levels: 100%:0%, 95%:5%, 90%:10%, and 85%:15%. The data were analyzed using ANOVA and Duncan's multiple range test for physicochemical parameters, while Kruskal-Wallis and Mann-Whitney tests were used for sensory data. The results indicated that most physicochemical attributes did not differ significantly, except for the b* color value of the coffee powder. Sensory analysis using Quantitative Descriptive Analysis (QDA) showed no significant differences in aroma, flavor, aftertaste, acidity, body, and balance, except for the overall hedonic score. The 85%:15% formulation received a neutral score (2.97) and showed strong antioxidant activity with an IC50 value of 27.02 ppm. Abstrak Biji mengkudu kaya akan antioksidan dan berpotensi dimanfaatkan sebagai pangan fungsional, salah satunya kopi biji mengkudu. Penelitian bertujuan untuk mengetahui pengaruh perbandingan kopi biji mengkudu dan kopi arabika terhadap karakteristik fisikokimia dan sensori. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) 1 faktor yaitu perbandingan kopi biji mengkudu dan kopi arabika dengan 4 taraf perlakuan (100%: 0%), (95%: 5%), (90%: 10%) dan (85%: 15%). Analisis data yang digunakan adalah ANOVA dan uji lanjut Duncan, serta Kruskal Wallis dan uji lanjut Mann Whitney’s. Hasil analisis fisikokimia menunjukkan tidak berbeda nyata, kecuali nilai b* bubuk kopi. Analisis sensori Quantitative Descriptive Analysis (QDA) menunjukkan karakteristik fragrance/aroma, flavor, aftertaste, acidity, body dan balance yang tidak berbeda nyata, kecuali nilai hedonik overall pada perlakuan (85%: 15%) yaitu 2,97 (netral). Produk kopi biji mengkudu dengan perbandingan kopi arabika terpilih yaitu 85%: 15% memiliki aktivitas antioksidan sangat kuat dengan nilai IC50 27,02 ppm.